Current Message Policies For Operational And Anesthesia Technicians In The Operating Room. A New Appraisal (Journal of Namibian Studies : History Politics Culture, 2022)
Effective communication is crucial for ensuring patient safety and optimizing workflow in the operating room (OR). This article explores communication strategies tailored to operational and anesthesia technicians, who play critical roles in supporting surgical procedures. Key communication techniques include clear and concise communication, preoperative briefings, anticipatory communication, closed-loop communication during procedures, and postoperative debriefing. By implementing these strategies, operational and anesthesia technicians can enhance teamwork, minimize errors, and contribute to improved patient outcomes.